2021
DOI: 10.4103/apjon.apjon-2099
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Resilience, Anxiety/Depression, and Quality of Life in Patients with Colorectal Cancer Undergoing Chemotherapy in Japan

Abstract: Objective: This study clarifies the relationship between resilience and anxiety and depression, quality of life (QOL), and other related factors that influence colorectal cancer patients undergoing chemotherapy. Methods: This cross-sectional study focused on outpatients with colorectal cancer undergoing chemotherapy. A questionnaire including the Connor-Davidson Resilience Scale, Hospital Anxiety and Depression Scale, the MOS 12-item Short-Form Health Survey, and items … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
9
0
1
Order By: Relevance
“…In that sense, it becomes fundamental to understand which psychosocial factors may play a role in the prevention of these conditions and its burdensome consequences. Resilience, perceived social support ( Zhao et al, 2020 ; Tamura, 2021 ), perceived family support ( Su et al, 2017 ) and family communication skills ( Park et al, 2022 ) have been reported in the literature as important protective factors for symptoms of depression and for the adaptation to this life-threatening event. To optimize the prevention of these neuropsychiatric disorders, clinicians and researchers need to be attentive, screen and monitor affective symptoms in patients with cancer ( Walker et al, 2014 ) and, additionally, understand and bolster the psychosocial resources available both for patients and their relatives ( Seiler and Jenewein, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, it becomes fundamental to understand which psychosocial factors may play a role in the prevention of these conditions and its burdensome consequences. Resilience, perceived social support ( Zhao et al, 2020 ; Tamura, 2021 ), perceived family support ( Su et al, 2017 ) and family communication skills ( Park et al, 2022 ) have been reported in the literature as important protective factors for symptoms of depression and for the adaptation to this life-threatening event. To optimize the prevention of these neuropsychiatric disorders, clinicians and researchers need to be attentive, screen and monitor affective symptoms in patients with cancer ( Walker et al, 2014 ) and, additionally, understand and bolster the psychosocial resources available both for patients and their relatives ( Seiler and Jenewein, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Resilience could influence the way patients deal with advanced cancer and treatments through a cognitive reevaluation of the circumstance and the identification of meaning, which finally facilitates adaptation to cancer and improved general well-being (Palacio & Arias, 2018 ). Unfortunately, patients with advanced cancer had only moderate levels of resilience (Kavak et al, 2021 ) due to concerns about death and suffering from side effects of treatments that resulted in physical and psychological pain (Tamura, 2021 ). Moreover, compared to other cancer stages, patients with advanced cancer reported the lowest level of resilience (Aman & Akhtar, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depressed persons are less able to maintain or restore their psychological adaptation when faced with stressful life events (Kumpfer, 1999 ). Depression was negatively correlated with resilience in lung cancer (Hu et al, 2018 ), mixed cancer (Mungase et al, 2021 ), and colorectal cancer (Tamura, 2021 ). Previous research examined the relationships, but investigations are scarce on the predicting ability of depression on resilience among adult patients with advanced cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous studies on the effects of reactive mood disorder on the survival time of glioma patients, but the results obtained differ and have not been unified ( 12 - 14 ). In recent years, studies have gradually recognized the important role of psychological resilience in patients with chronic diseases and malignant tumors ( 15 - 17 ). Psychological resilience refers to the ability of an individual to recover from negative experiences and flexibly adapt to a changing external environment.…”
Section: Introductionmentioning
confidence: 99%